The Role of the Cullin-5 E3 Ubiquitin Ligase in the Regulation of Insulin Receptor Substrate-1 - Christine Zhiwen Hu; Jaswinder K. Sethi; Thilo Hagen (Biochemistry Research International)
Background. SOCS proteins are known to negatively regulate insulin signaling by inhibiting insulin receptor substrate-1 (IRS1). IRS1 has been reported to be a substrate for ubiquitin-dependent proteasomal degradation. Given that SOCS proteins can function as substrate receptor subunits of Cullin-5 E3 ubiquitin ligases, we examined whether Cullin-5 dependent ubiquitination is involved in the regulation of basal IRS1 protein stability and signal-induced IRS1 degradation. Findings. Our results indicate that basal IRS1 stability varies between cell types. However, the Cullin-5 E3 ligase does not play a major role in mediating IRS1 ubiquitination under basal conditions. Protein kinase C activation triggered pronounced IRS1 destabilization. However, this effect was also independent of the function of Cullin-5 E3 ubiquitin ligases. Conclusions. In conclusion, SOCS proteins do not exert a negative regulatory effect on IRS1 by functioning as substrate receptors for Cullin-5-based E3 ubiquitin ligases both under basal conditions and when IRS1 degradation is induced by protein kinase C activation.